1, 2(2, 2-dihydroxy Benzelidenamine) Phenyl Complexes as Corrosion Inhibitor for Carbon Steel in Hydrochloric Acid - Najeeb, Dina A; Salman, Taghried A (Al-Nahrain Journal of Science, 2018)
The corrosion inhibition on carbon steel in 1MHCl by 1, 2(2, 2-dihydroxy benzelidenamine) phenyl and its complexes was studied at different concentrations by "weight loss method". Data mark, for the compound shows good performance. These measurements show that the inhibition efficiency obtained by these complexes increased by increasing their concentration. The inhibition efficiency follow the order Co>Ni>Cu. The activation and adsorption thermodynamic parameters were determined and discussed. The surface coverage (Ɵ) of the inhibitors conform "Langmuir adsorption isotherm". (Morphology) of the carbon steel alloy has been examine using "scanning electron microscopy" in existence and inexistence of inhibitor.